Pendidikan Aqidah Di Rumah Tangga - Hasballah, Jamaliah (Intelektualita: Journal of Education Sciences and Teacher Training, 2015)
â€˜Aqidah means belief which is tightly bound strong and knotted in oneâ€™s soul. Belief in God is a solid bond that should not be opened or removed for granted because the impact is very great for human life. Solid ties that bind his mind, his heart, his behavior to God, implement all the commandments, and leave all the prohibitions. â€˜Aqidah as a solid bond that is could lead children into a balance life (tawazun). If only I may be illustrated, I would say that divinity is immunization for a disease, because in this life many temptation faced by children, faced by various trials, it sometimes makes him despair, broken heart, his soul shaken even the stress and suicide. People who do not have a solid bond with God will cause tempted to the other ties easily that would harm himself. As the Word of God in surah Luqman verse 13 which mean:â€ Behold, Luqman said to his son by way of instruction: â€œO my son! join not in worship (others) with Allah: for false worship is indeed the highest wrong-doing.â€